Design Of Digitalization Of Lamong Bay Terminal Service System In Supporting Indonesian Sea Toll Program With Quality Function Deployment (Qfd) Approach - Cahyawati, Amanda Nur (Journal of Innovation and Applied Technology, 2022)
Indonesia is a maritime country because it has a larger water area than land area. Indonesia has 17,499 islands that inhabit 3.25 million km2 of water from Sabang to Merauke. Therefore, sea transportation is one of the most important things that is used as a link between islands in Indonesia. Seaports are one of the most important parts of the marine transportation network in Indonesia in supporting the transportation of people and goods. Sea toll is a marine logistical transportation concept that aims to connect major ports in the archipelago. With this sea toll, it is hoped that it can reduce logistics costs and can maintain the stability of the price of goods and commodities between regions.